2007
DOI: 10.1002/jor.20400
|View full text |Cite
|
Sign up to set email alerts
|

Myeloperoxidase and chlorinated peptides in osteoarthritis: potential biomarkers of the disease

Abstract: Osteoarthritis (OA) is a disabling condition in which multiple initiating events or conditions (heritable and nonheritable) result in eventual loss of articular cartilage. However, the etiology of OA remains poorly understood, and diagnosis of early disease is difficult due to the lack of specific identifiers. Recent literature suggests that a series of inflammatory processes may be involved in initiating and propagating OA. We hypothesized that products of neutrophils and macrophages, namely myeloperoxidase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
134
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(135 citation statements)
references
References 28 publications
(25 reference statements)
0
134
0
1
Order By: Relevance
“…Consistent with the idea that a large amount of hypochlorite may be generated in vivo during inflammation, extracellular myeloperoxidase is also estimated to reach millimolar concentrations (33), and using computational modeling, it is predicted that proteins from atherosclerotic plaques are exposed to a 20-fold molar excess of hypochlorite over their lifetime (32). In addition, it is very clear that proteins are modified by hypochlorite in vivo and that the extent of these modifications is increased in many disease states, including atherosclerosis (40), Alzheimer's disease (5), kidney disease (49), rheumatoid arthritis (45), osteoarthritis (50), and chronic lung disease (51).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the idea that a large amount of hypochlorite may be generated in vivo during inflammation, extracellular myeloperoxidase is also estimated to reach millimolar concentrations (33), and using computational modeling, it is predicted that proteins from atherosclerotic plaques are exposed to a 20-fold molar excess of hypochlorite over their lifetime (32). In addition, it is very clear that proteins are modified by hypochlorite in vivo and that the extent of these modifications is increased in many disease states, including atherosclerosis (40), Alzheimer's disease (5), kidney disease (49), rheumatoid arthritis (45), osteoarthritis (50), and chronic lung disease (51).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Marla J. Steinbeck et al 1 showed that HOCl and Cl 2 oxidize pyridinoline (PYD) compounds to form chlorinated moieties 6 . PYD crosslinks are integral members in the structural composition of articular cartilage that serve to covalently link helical regions of Col-II to one another, type IX collagen (Col-IX) to the surface of Col-II, and Col-IX to other molecules of Col-IX.…”
Section: Figure 1: Biochemical Basis Of Articular Cartilage Degradationmentioning
confidence: 99%
“…Recently in a study Patients with early OA demonstrated significantly elevated levels of MPO in synovial fluid 1 . Patients in the control and advanced OA groups demonstrated little elevation in MPO levels.…”
Section: Introductionmentioning
confidence: 97%
“…Steinbeck, 2007). According to World Health Organization (WHO) osteoarthritis is a serious disabling disease, statistically 1 in 10 developed countries are under its influence.…”
Section: Introductionmentioning
confidence: 99%